End-to-end chiller fault diagnosis using fused attention mechanism and dynamic cross-entropy under imbalanced datasets. (15th March 2022) - Han, Songyu; Shao, Haidong; Huo, Zhiqiang; Yang, Xingkai; Cheng, Junsheng
Abstract: Fault diagnosis techniques play an increasingly important role in the operation and maintenance of smart city systems. Artificial intelligence improves the efficiency of chiller system fault diagnosis, and greatly reduces the energy consumption of urban buildings. The existing intelligent fault diagnosis methods of chiller mostly rely on balanced training datasets; lacking fault samples makes these methods incompetent to extract reliable features to recognize abnormal machine conditions, resulting in the degraded performance. To overcome the deficiencies of reported studies, a new method, called end-to-end chiller fault diagnosis, is proposed using a fused attention mechanism and dynamic cross-entropy. Firstly, a one-dimensional convolution network (1D-CNN) and long-short term memory (LSTM) are combined to capture the spatial-temporal features from the original data directly. Afterwards, a fused attention mechanism is developed to further refine the extracted features to increase the contribution of crucial features and achieve high-quality diagnostic information mining. Finally, the dynamic cross-entropy (DCE) is designed for updating the imbalance factor in real-time, with more focus on the hard-classified types. The experimental analysis results demonstrate the feasibility and superiority of the proposed method in identifying chiller system faults with imbalanced datasets. Graphical abstract: Image 1 Highlights: 1D–CNN–LSTM is constructed to directly mine spatial-temporal information. Fused attention mechanism is developed to further mine representative features. Dynamic cross-entropy is designed to flexibly adjust the imbalanced factor. Two case studies prove the feasibility and superiority of the proposed method.